Peningkatan Hasil Belajar Peserta Didik Menggunakan Pendidikan Matematika Realistik Indonesia (PMRI) pada Materi Keliling dan Luas Bangun Datar di Kelas V SDN 14 Kampung Jambak Padang - Eldini, Fanisa Khaira; Masniladevi, Masniladevi (Indo-MathEdu Intellectuals Journal, 2025)
This research originated from the unoptimal planning and implementation of learning the perimeter and area of flat shapes, causing the learning outcomes of students in class V SDN 14 Kampung Jambak Padang to not reach the desired criteria. The purpose of this study was to describe the improvement of learning outcomes regarding the perimeter and area of flat shapes through the application of Indonesian Realistic Mathematics Education (PMRI) in class V SDN 14 Kampung Jambak. This study used classroom action research (PTK) with qualitative and quantitative approaches conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. Observation, tests, and non-tests were the data collection methods used. This study involved 27 students and educators from class V SDN 14 Kampung Jambak. Student learning outcomes averaged 80.72% (C) in the first cycle, and increased to 90.65% (B) in the second cycle. In realistic mathematics education (PMRI), learning outcomes of perimeter and area of flat shapes in elementary school can be improved